1997
DOI: 10.1093/jn/127.7.1339
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Damage to the Respiratory Epithelium Induces Acute Phase Changes in Vitamin A Metabolism without Depleting Retinol Stores of South African Children , ,

Abstract: Whereas there is much information concerning the effects of vitamin A status on response to infectious challenge, the effects of infection or trauma on vitamin A metabolism and status are less well documented. These relationships need to be understood to optimize clinical and public health programs to improve vitamin A status and health of children in less-developed countries. We measured acute changes in retinol and retinol-binding protein in 57 young South African children hospitalized following respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
0
30
1
Order By: Relevance
“…However, in children, serum retinol concentrations are suppressed by~25% during common infections (23,124,148) and up to 69% in children with Shigellosis (127). This decrease in serum retinol concentration is independent of vitamin A liver reserves (173). Therefore, individuals who are experiencing infection but have an adequate vitamin A status may be misclassified as deficient, leading to overestimation of deficiency prevalence in a population.…”
Section: Apps As Markers Of Infection For Nutrition Interventionsmentioning
confidence: 99%
“…However, in children, serum retinol concentrations are suppressed by~25% during common infections (23,124,148) and up to 69% in children with Shigellosis (127). This decrease in serum retinol concentration is independent of vitamin A liver reserves (173). Therefore, individuals who are experiencing infection but have an adequate vitamin A status may be misclassified as deficient, leading to overestimation of deficiency prevalence in a population.…”
Section: Apps As Markers Of Infection For Nutrition Interventionsmentioning
confidence: 99%
“…18 While boys in school in South Africa were found to have a serum retinol level below the recommended level, 19 a sample taken from South-African hospitals found no significant difference by gender. 20 Consequently, the a priori assumption that boys are always more at risk than girls requires revisiting. Of the 35 studies in which boys do not have more deficiencies than girls, 25 (71%) found no significant differences.…”
Section: Vitamin Amentioning
confidence: 99%
“…In acute phase reaction, there is a transient decrease in the production of small molecular weight proteins, including RBP, and an increase in the permeability of renal epithelial cells. Decreased vitamin A might also be due to increased uptake of retinol by certain tissues 25 . PRI could be reduced through three main pathways: promotion of wound healing; increased resistance to infection; and immune enhancement if infection occurs.…”
Section: Resultsmentioning
confidence: 99%